The impact of SGLT2 inhibitors on αKlotho in renal MDCK and HK-2 cells - Wolf, Lisa; Föller, Michael; Feger, Martina (Frontiers in Endocrinology, 2023)
αKlotho is a transmembrane protein predominantly expressed in the kidney serving as a co-receptor for phosphate homeostasis-regulating hormone FGF23 and has an extracellular domain that can be cleaved off and is a hormone. αKlotho deficiency results in accelerated aging and early onset of aging-associated diseases while its overexpression strongly expands the lifespan of mice. Moreover, αKlotho exerts health-beneficial anti-inflammatory, anti-neoplastic, anti-fibrosis, anti-oxidant effects. Higher αKlotho levels are associated with better outcomes in renal and cardiovascular diseases. SGLT2 inhibitors are novel drugs in the treatment of diabetes by inhibiting renal glucose transport and have additional nephro- and cardioprotective effects. We explored whether SGLT2 inhibitors affect αKlotho gene expression and protein secretion. Experiments were performed in renal MDCK and HK-2 cells, and αKlotho transcripts were determined by qRT-PCR and Klotho protein by ELISA. SGLT2 inhibitors canagliflozin, sotagliflozin, and dapagliflozin enhanced whereas empagliflozin reduced αKlotho gene expression in MDCK cells. By the same token, canagliflozin, sotagliflozin, dapagliflozin, but not empagliflozin down-regulated p65 subunit of pro-inflammatory NFκB. In HK 2 cells, all SGLT2 inhibitors reduced αKlotho transcripts. Canagliflozin and sotagliflozin, however, increased Klotho protein concentration in the cell culture supernatant, an effect possibly due to up-regulation of ADAM17. Taken together, our investigations demonstrate complex effects of different SGLT2 inhibitors on αKlotho gene expression and protein secretion in renal MDCK and HK 2 cells.